ANALISIS PERTANGGUNGJAWABAN PIDANA TERHADAP PENGGUNAAN ARTIFICIAL INTELIGENCE SEBAGAI ALAT TINDAK KEJAHATAN DI INDONESIA - Yohana Lastrio; Orpa G Manuain; Ngongo Dede (Petitum Law Journal, 2026)
The rapid advancement of Artificial Intelligence (AI) has brought transformative benefits across various sectors but has also introduced profound legal challenges, particularly in attributing criminal liability when AI is used as a tool in criminal acts. This research is guided by the core question: How can Indonesia’s criminal law system establish liability for the use of Artificial Intelligence as an instrument of crime? Employing a normative juridical method, this study integrates statutory, conceptual, case-based, comparative, and historical approaches to examine the current legal framework, including the Electronic Information and Transactions Law (ITE Law) and the 2023 Indonesian Criminal Code. Findings reveal that Indonesia’s legal system still faces significant normative and technical barriers. Normatively, existing regulations do not fully address the complexity of autonomous and adaptive AI systems. Technically, establishing mens rea and causality between human action and AI-generated outcomes remains difficult. In this context, the Perpetration by Another Liability model is a relevant legal framework, positioning AI as instrumentum delicti and assigning criminal responsibility to the human actors, developers, providers, or users, who knowingly deploy AI systems for unlawful purposes. This model aligns with Articles 36 and 37 of the Criminal Code and emphasizes accountability, precaution, and legal adaptability in facing the evolving nature of AI-driven crimes.